Sentinel lymph node biopsy provides better regional control than observation in early stage maxillary squamous cell carcinoma - Wang, Yannan; Zhang, Xu; Yuan, Junhui; Zhou, Zhengquan; Du, Wei; Liu, Fei; Wang, Jing (Frontiers in Oncology, 2025)
BackgroundAn observational approach in the management of the cervical region in instances of maxillary squamous cell carcinoma (SCC) results in appreciable treatment failure, necessitating a more efficacious neck intervention. Our objective was to compare the efficacy of sentinel lymph node biopsy (SLNB) versus observation regarding regional control (RC) in patients diagnosed with cT1/2N0 maxillary SCC.MethodsPatients who underwent SLNB or observation for neck management in primary cT1/2N0 maxillary SCC were retrospectively enrolled. SLNB was performed one day before surgery using 99mTc-nanocolloid, with the decision to proceed with neck dissection guided by intraoperative sentinel lymph node pathology. Primary outcome variable was 5-year RC. Impact of neck management on RC was evaluated using Kaplan-Meier survival analysis and Cox proportional hazards modeling.ResultsA total of 145 patients were included, with SLNB performed in 46 necks and observation applied to 99 cases. Sentinel lymph nodes were successfully identified in all instances. In comparison, regional recurrence was observed in eight patients within the SLNB cohort, of whom six had previously exhibited a metastatic sentinel lymph node, as opposed to 21 patients in the observational group. In the Cox model, SLNB was associated with a relative 28% reduction in the risk of neck failure compared to observation (p=0.021). Occult lymph node metastasis was more prevalent in tumors possessing a diameter exceeding 2cm or a depth of invasion surpassing 4mm, subgroup analysis revealed that the positive impact of SLNB on outcomes became statistically significant only for tumors larger than 2.0 cm (p=0.041, hazard ratio=0.23, 95% confidence interval: 0.05-0.98) or with a depth of invasion greater than 4.0 mm (p=0.042, hazard ratio=0.22, 95% confidence interval: 0.02-0.95).ConclusionSLNB demonstrated superior RC compared to observation in patients diagnosed with cT1/2N0 maxillary SCC. These results support reconsidering SLNB as a standard approach among those with tumors exceeding 2.0 cm in size or a depth of invasion surpassing 4.0 mm.